Colonic diverticulosis - diagnostic and therapeutic difficulties - Cristian Meșină; Theodor Viorel Dumitrescu; Mihai Calin Ciorbagiu; Cosmin Vasile Obleaga; Ionica-Daniel Vilcea; Mihaela-Iustina Mesina-Botoran (Journal of Mind and Medical Sciences)
Objectives. The objectives of this study are to highlight the diagnostic and therapeutic difficulties in patients with complicated acute colonic diverticulosis. Methods. The study group comprised 40 patients hospitalized to the Second Surgical Clinic of the Emergency County Hospital in Craiova, Romania, through the emergency service between 2015 and 2021. Regarding the sex distribution of the patients with colonic diverticular disease studied, there was a predominance of males. The distribution of patients was as follows: 22 patients with acute colonic diverticulitis, out of whom 21 patients suffered from left acute colonic diverticulitis and 1 patient suffered from right acute colonic diverticulitis. Results. The diagnosis of acute colonic diverticulitis was made by corroborating the data obtained on the objective clinical examination with the data obtained by exploring the abdomen by means of computed tomography, which revealed a thickening of the colon wall (acute sigmoid diverticulitis predominated). The treatment applied to patients with acute diverticulitis was conservative and in patients with acute perforated colonic diverticulitis, the treatment of choice was the surgical one. Mortality was 7.5% of all the cases. Conclusions. In patients with perforated colonic diverticular disease, the administered treatment consisted in Hartmann segmental colectomy, wound care, peritoneal drainage. The reintegration of the colon in the digestive transit was performed after 3-6 months.